1973
DOI: 10.1073/pnas.70.6.1659
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotypic Control by Cyclic AMP: Interaction with Cyclic GMP and Possible Role of Microtubules

Abstract: Previous studies have shown that exogenous dibutyryl cyclic AMP inhibits the uptake of uridine, leucine, and 2-deoxyglucose by cultured mouse fibroblasts. 3':5'-cyclic GMP is shown here to counteract these inhibitory effects as well as the inhibition ofprecursor transport and leucine incorporation into proteins produced by prostaglandin E1. We conclude, therefore, that cyclic GMP antagonizes the "pleiotypic" effects of cyclic AMP in these cells.Colcemid and vinblastine, but not cytochalasin B., reverse the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

1974
1974
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(51 citation statements)
references
References 24 publications
(32 reference statements)
2
49
0
Order By: Relevance
“…In studies with rat mammary gland explants in culture [2] cyclic AMP inhibited the increase of enzyme activities normally associated with lactogenesis, in particular the activities of those enzymes involved in lipogenesis, and also markedly depressed the synthesis of DNA, RNA and fatty acids. This analogy with the pleiotypic response observed for other cells grown in culture [3], and the reversal by cyclic GMP of the pleiotypic inhibition of 3T3 cells treated with dibutyryl cyclic AMP [4] , led us to investigate the simultaneous fluctuations of both cyclic nucleotides throughout the lactation cycle. differentiation of the mammary gland during pregnancy, its response to hormones and the promotion of specific cell programmes for the synthesis of the characteristic components of milk may all be mediated by modification of the ratio between the two nucleotides.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In studies with rat mammary gland explants in culture [2] cyclic AMP inhibited the increase of enzyme activities normally associated with lactogenesis, in particular the activities of those enzymes involved in lipogenesis, and also markedly depressed the synthesis of DNA, RNA and fatty acids. This analogy with the pleiotypic response observed for other cells grown in culture [3], and the reversal by cyclic GMP of the pleiotypic inhibition of 3T3 cells treated with dibutyryl cyclic AMP [4] , led us to investigate the simultaneous fluctuations of both cyclic nucleotides throughout the lactation cycle. differentiation of the mammary gland during pregnancy, its response to hormones and the promotion of specific cell programmes for the synthesis of the characteristic components of milk may all be mediated by modification of the ratio between the two nucleotides.…”
Section: Introductionmentioning
confidence: 71%
“…Some of these activities may be highly relevant to the mammary gland a) the role of cyclic AMP as promoter of differentiation could be of special significance to the development of the gland during pregnancy, a stage at which the level of this nucleotide is high; b) the rise of cyclic GMP after the onset of lactation may explain the wave of mitosis which follows shortly after parturition in the rat [23], a process which is also significant (in addition to increasing the number of secretory cells present) in that it may, as suggested by Stockdale and Topper [24] , make these cells specially susceptible to environmental factors capable of modifying the metabolic pattern; c) the complex endocrine control of the mammary gland and the tissue response to hormones may be expressed through the dualistic system of opposing cyclic AMP and cyclic GMP levels which could, as has already been shown for other cells grown in culture [3,4] , also modulate the pleiotypic control of mammary cells [2] .…”
Section: Resultsmentioning
confidence: 99%
“…The possible relationship of CDR to Ca2+-dependent guanylate cyclase activity (23) requires systematic exploration. In spite of these limitations, the potential applicability of the present findings to the bidirectional cyclic nucleotide control of cell proliferation (22,24,25) should be noted. Anderson and Pastan (26) have evidence for the existence of an adenylate cyclase activating factor that is present in fibroblasts grown in culture.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments also indicate that this inhibition may be associated with the decrease in cell division caused by PGE1. A similar action by PGE1, that of inhibiting serum-stimulated uptake of uridine in 3T3 cells, was also noted by Kram & Tomkins (1973). This activity by PGE1 may indeed be a part of a synchronized effect on the metabolic events leading to incubation; o, -E1-24, corresponding cultures not treated with PGE1.…”
Section: Resultsmentioning
confidence: 75%
“…For example, Kram & Tomkins (1973) demonstrated that after serum stimulation, those cultures of Balb/c 3T3 cells that included PGE1 exhibited a much lower uptake ofleucine, uridine and adenosine than did the cultures to which PGE1 was not added. PGE1 is capable of reversibly decreasing cell division and the incorporation of [3H]thymidine into DNA in the WI38 human embryo lung fibroblasts (Kurtz et al, 1974).…”
mentioning
confidence: 99%